2013
DOI: 10.1073/pnas.1300558110
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of the yeast N -acetyltransferase Mpr1 involved in oxidative stress tolerance via proline metabolism

Abstract: Mpr1 (sigma1278b gene for proline-analog resistance 1), which was originally isolated as N-acetyltransferase detoxifying the proline analog L-azetidine-2-carboxylate, protects yeast cells from various oxidative stresses. Mpr1 mediates the L-proline and L-arginine metabolism by acetylating L-Δ 1 -pyrroline-5-carboxylate, leading to the L-arginine-dependent production of nitric oxide, which confers oxidative stress tolerance. Mpr1 belongs to the Gcn5-related N-acetyltransferase (GNAT) superfamily, but exhibits p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Proline might protect cells from acid-induced oxidative stress by the following contribution. Overexpressed Mpr1 (encoding N-acetyltransferase which detoxifies proline-analogue compound) may lead to decreased ROS and increased cell viability (67,68). Proline is also suggested to act as a scavenger of more reactive oxidative stress compounds produced under acid stress conditions, such as hydroxy radicals ( OH) (69), which are caused by lactate induction (anion) via Fenton reaction (70,71).…”
Section: Accumulation Of Gsh Along With Amino Acids Involved In Gsh Smentioning
confidence: 99%
“…Proline might protect cells from acid-induced oxidative stress by the following contribution. Overexpressed Mpr1 (encoding N-acetyltransferase which detoxifies proline-analogue compound) may lead to decreased ROS and increased cell viability (67,68). Proline is also suggested to act as a scavenger of more reactive oxidative stress compounds produced under acid stress conditions, such as hydroxy radicals ( OH) (69), which are caused by lactate induction (anion) via Fenton reaction (70,71).…”
Section: Accumulation Of Gsh Along With Amino Acids Involved In Gsh Smentioning
confidence: 99%
“…Our previous study revealed that Mpr1 forms a dimer in solution (13). In the crystal structure, Asn203 is located at the interface of two molecules of Mpr1, which seem to be a pair of dimers.…”
Section: Resultsmentioning
confidence: 94%
“…A recent structural analysis clarified the mechanism by which the substitution of Leu for Phe65 increases the thermostability of Mpr1, and also provided clues to the design of novel mutations for improvement of the enzymatic functions (13). Here, we successfully constructed new stable Mpr1 variants by structure-based molecular design, and indicated that some of them had increased abilities to contribute to L-arginine biosynthesis.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations